Full-Scale Tests for Assessing Blasting-Induced Vibration and Noise - Chung-Won Lee; Jiseong Kim; Gi-Chun Kang (Shock and Vibration)
Vibration and noise problems caused by a number of construction processes, specifically blasting for infrastructure development, are becoming important because of their civil appeal. In this study, a square root equation (SRE) with a 95% confidence level was proposed for predicting blasting-induced vibration through full-scale test blasting, and the vibration value predicted from this equation was located between the values predicted from the USBM (US Department of Interior, Bureau of Mines), NOF (Nippon Oil & Fats Co., Ltd.), and MCT (Ministry of Construction and Transportation) equations. Additionally, by comparing the measured noise level at full-scale test blasting with the calculated noise levels from several noise prediction equations, it was determined that the noise level predicted by the ONECRC equation had the best agreement with the measured results. However, in cases where blasting includes tunnel excavation, simultaneous measurement of vibration and noise is required to prevent damage to the surrounding facilities.